2013
DOI: 10.3390/ijms140611742
|View full text |Cite
|
Sign up to set email alerts
|

Modulation by Melatonin of the Pathogenesis of Inflammatory Autoimmune Diseases

Abstract: Melatonin is the major secretory product of the pineal gland during the night and has multiple activities including the regulation of circadian and seasonal rhythms, and antioxidant and anti-inflammatory effects. It also possesses the ability to modulate immune responses by regulation of the T helper 1/2 balance and cytokine production. Autoimmune diseases, which result from the activation of immune cells by autoantigens released from normal tissues, affect around 5% of the population. Activation of autoantige… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
55
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(57 citation statements)
references
References 150 publications
(143 reference statements)
0
55
0
2
Order By: Relevance
“…Similarly, in our study using CIA C57BL/6J mice, intraperitoneal melatonin treatment (10 and 30 mg/kg) ameliorated paw swelling, cartilage degradation, and bone erosion, as well as the production of TNF‐α and IL‐1β. These conflicting observations may result from the different doses of melatonin or various RA animal models used in the investigations . The relationship between melatonin and RA requires further research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, in our study using CIA C57BL/6J mice, intraperitoneal melatonin treatment (10 and 30 mg/kg) ameliorated paw swelling, cartilage degradation, and bone erosion, as well as the production of TNF‐α and IL‐1β. These conflicting observations may result from the different doses of melatonin or various RA animal models used in the investigations . The relationship between melatonin and RA requires further research.…”
Section: Discussionmentioning
confidence: 99%
“…Melatonin has also shown immunomodulatory activity in T helper (Th)1/2 development . Furthermore, beneficial effects have been reported from investigations involving melatonin in animal models and clinical trials of various autoimmune diseases, such as multiple sclerosis, systemic lupus erythematosus, and inflammatory bowel disease, amongst others …”
Section: Introductionmentioning
confidence: 99%
“…Several studies have indicated that melatonin may decrease the production of pro-inflammatory cytokines and inhibit the expression the pro-inflammatory enzymes iNOS and COX-2 in cells of the liver and lung of LPS-treated rats (Crespo et al, 1999, Esposito and Cuzzocrea, 2010, Mauriz et al, 2012, Lin et al, 2013). It has been suggested that melatonin protects against developing white matter damage by inhibiting microglial activation and oligodendroglial maturation, and these effects appear to be melatonin-receptor dependent (Olivier et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Разом з тим при його сумісному використанні з мелатоніном спостерігалася виразна коригувальна дія. Подібне потенці-ювання може пояснюватися комплексним ха-рактером впливу мелатоніну [10], в тому чис-лі й при атопічних алергічних станах [11] та його здатністю до корекції хронобіологічних процесів в організмі [10], які мають важливе значення для реалізації ефектів ДСІП [1,8].…”
Section: результати та їх обговоренняunclassified